2014 IEEE 32nd International Conference on Computer Design (ICCD) 2014
DOI: 10.1109/iccd.2014.6974710
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous block architecture

Abstract: This paper makes two new observations that lead to a new heterogeneous core design. First, we observe that most serial code exhibits fine-grained heterogeneity: at the scale of tens or hundreds of instructions, regions of code fit different microarchitectures better (at the same point or at different points in time). Second, we observe that by grouping contiguous regions of instructions into blocks that are executed atomically, a core can exploit this heterogeneity: atomicity allows each block to be executed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Prior work on the existence of phases at ne granularity and their potential micromanagement has shown that it is possible to exploit their bene ts through a heterogeneous system with di erent back-ends sharing the same front end [12,[20][21][22]. Despite the claim, no experimental data is provided that reveals the actual existence of application phases that appear at a ne granularity nor are the circumstances under which they can be exploited explained.…”
Section: Related Workmentioning
confidence: 85%
See 2 more Smart Citations
“…Prior work on the existence of phases at ne granularity and their potential micromanagement has shown that it is possible to exploit their bene ts through a heterogeneous system with di erent back-ends sharing the same front end [12,[20][21][22]. Despite the claim, no experimental data is provided that reveals the actual existence of application phases that appear at a ne granularity nor are the circumstances under which they can be exploited explained.…”
Section: Related Workmentioning
confidence: 85%
“…To reduce overall system slowdown when migrating, several studies propose the implementation of dedicated hardware to e ciently handle the transfer without any so ware intervention [12,13,18,21,26] and also fusing cores to share the front-end [20,22,24]. However, as hybrid designs are too complex to implement, it is worth investigating a simpler approach determining which components contribute most to the bene ts and sharing only those.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varied voltage and frequency settings are used to create performance and power heterogeneity. Fallin et al uses customized atomic blocks to examine extremely finegrained heterogeneity [8]. Our solution combines the benefits of both architectural heterogeneity [20] and fast migration of only register state, and contributes a more sophisticated mechanism to estimate the inactive core's performance.…”
Section: Heterogeneous Cores Migratory Threadsmentioning
confidence: 97%
“…DMPs contain hardware which can be modi ed post fabrication. Mitall's survey [14] de nes three types of modi able resources: the core count [9], number of resources that each core has [8] and microarchitectural features [1,7,21]. In our paper we focus on DMPs that modify the core count.…”
Section: Dynamic Multicore Processormentioning
confidence: 99%